2013
DOI: 10.1111/1462-2920.12070
|View full text |Cite
|
Sign up to set email alerts
|

Self‐suppression of biofilm formation in the cyanobacterium Synechococcus elongatus

Abstract: Biofilms are consortia of bacteria that are held together by an extracellular matrix. Cyanobacterial biofilms, which are highly ubiquitous and inhabit diverse niches, are often associated with biological fouling and cause severe economic loss. Information on the molecular mechanisms underlying biofilm formation in cyanobacteria is scarce. We identified a mutant of the cyanobacterium Synechococcus elongatus, which unlike the wild type, developed biofilms. This biofilm-forming phenotype is caused by inactivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
117
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(123 citation statements)
references
References 52 publications
2
117
4
Order By: Relevance
“…1b) and cryo-scanning electron microscopy (cryo-SEM, Fig. 1c) substantiate biofilm development by T2SEΩ (see Schatz et al 33. for additional cryo-SEM as well as environmental-SEM analyses).…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…1b) and cryo-scanning electron microscopy (cryo-SEM, Fig. 1c) substantiate biofilm development by T2SEΩ (see Schatz et al 33. for additional cryo-SEM as well as environmental-SEM analyses).…”
Section: Resultssupporting
confidence: 52%
“…Previously, we demonstrated that inactivation of genes encoding homologs of type II protein secretion systems or the type IV pilus assembly apparatus (components of these complexes share a high degree of similarity34353637) impairs a biofilm inhibitory mechanism of S. elongatus and enables biofilm development33. Inactivation of synpcc7942_2071, which encodes a homolog of subunit E of type II secretion systems (T2SE), results in a mutant (T2SEΩ) that adheres to the growth tube in contrast to the planktonic phenotype of the WT strain (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with heterotrophic bacteria, there is little information about biofilm formation in cyanobacteria (Parnasa et al, 2016). However, recent studies have shown that Synechocystis and Synechococcus elongatus PCC 7942 also exhibit variations in gene expression pattern when grown on a solid surface or in liquid (Nakasugi and Neilan, 2005;Schatz et al, 2013;Agostoni et al, 2016). Interestingly, the Synechocystis strain used in this study, which is not identified as Glc tolerant, grew well in liquid BG11 supplemented with Glc concentrations from 0.2 to 20 mM (Supplemental Fig.…”
Section: Is Stationary Phase Reached Because Of Metabolic/ Nutrient Lmentioning
confidence: 81%
“…In the case of Chlamydia trachomatis, one of these genes has been linked to protein secretion (20), suggesting that there may be different subclasses of T2S that deviate from the canonical system present in the Proteobacteria. In Synechococcus elongatus belonging to the Cyanobacteria, a T2S E-like gene has been linked to protein secretion; however, this gene may be encoding a component of a type IV pilus rather than a T2S apparatus (19,23). So far, genome database analyses have failed to reveal any evidence for potential T2S systems in Bacteroidetes, Chlorobi, Fusobacteria, or Verrucomicrobia (10,19).…”
mentioning
confidence: 99%